Avaliação da mobilidade dos colifagos F-específicos presentes em efluentes sanitários aplicados em um latossolo vermelho - Guilherme Tadeu de Melo Espeschit (2021)
Land treatment of wastewater is a very important alternative for common wastewater treatment, mainly considering sanitary aspects, soil and groundwater quality. The major difference between this technique and others of final disposal of effluents is the possibility of nutrients is the nutrients reclamation, mostly nitrogen and phosphate, besides groundwater recharge, high removal rates of COD, suspended solids and pathogens. However, there are a few studies evaluating groundwater contaminations of virus and its transport. Because of its size, resembling colloids, most virus are not filtered in soil, reigning inactivation and adsorption mechanisms. The present research objectives to evaluate the transport and possibility of enteric virus contamination in groundwater using F+ coliphages as indicators, since their structures are similar, they cannot replicate in watercourse and its analysis is robust, fast and cheap. Breakthrough curves from an UASB effluent disposed in three saturated soil columns were modeled, one of them having a raw oxisol (SB) and the others, mixtures of it and sand (S30- 30% and S-60-60% added). The software Hydrus-1D was used for the analysis and calibration using a unidimensional model derived from the advection-dispersion-adsorption-inactivation equation. Besides F+ coliphage concentration, EC was monitored through the experiments overtime for comparison between virus and ions mobility. After calibration, vertical profiles with 100 m were simulated for estimating the plume reach beneath. The mixtures SB, S30 and S60 presented, respectively, retardation factors of 0,62, 0,72 and 0,75 PV. The modeled breakthrough curves presented R² between 0,6 and 0,9. Obtained results indicate an increase in mobility with sand added and high risk of virus contamination of groundwater, even in profiles with 100 meters of depth. It is necessary to evaluate the horizontal transport of virus and use undisturbed samples of different soils for a more precise evaluation.